A critical analysis of the relationships of national goals, educational aims and educational objectives of primary school teacher training centre programs in Nepal - Pradhan, Ratnan Lal 1937- (s.n.], 1972)
This paper is an analysis of the national goals and national educational aims as they relate to objectives of curricular programs of primary teacher training institutions. Results of this study indicate how national development goals, educational aims and objectives on the macro-level may be linked to national development.